Modern evaluation instruments in education - Alarilla, Luis M.
Anecdotal reports or ratings, interview, questionnaire, rating device, sociometric technique, and cumulative record are some of the instruments used in modern evaluation in education. Proper use plus a good knowledge of the statistical procedures in the interpretation of their results would mean systematic guidance and an excellent follow-up of the educational progress of every student in our educational system.
Keywords: Educational evaluation; Educational tests and measurements